The NuA4/TIP60 histone-modifying complex and Hr78 modulate the Lobe2 mutant eye phenotype - Stonbraker Madison P.; DePaul Dominic A.; Heidel-Roberts Ethan C.; Greene Hallee; Johnson Matthew Logan (Open Life Sciences)
Gene regulation is important during tissue formation, but redundant systems make it difficult to study in vivo. The protein Jazf-1 is a member of the NuA4/TIP60 histone-modifying complex, and a transcriptional repressor has been suggested to be important for Drosophila melanogaster eye development. We used the GAL4-UAS system to determine the impact of altering gene expression. GAL4-UAS manipulations of Jazf-1 in the eye caused variable and not fully penetrant phenotypes. Increased expression of Jazf-1 has been shown to suppress a Lobe 2 small eye phenotype. We found that Lobe 2 produces a sensitive background for an in vivo assay to monitor gene regulatory complexes. Depleting Jazf-1 and other NuA4/TIP60 complex members significantly enhanced the eye phenotype. We also tested Hr78, which directly interacts with Jazf-1, and found it inversely modifies the Lobe 2 phenotype. An Hr78 mutation predicted to uncouple the Jazf-1 interaction but still capable of interactions with transcriptional activators further enhanced the Lobe 2 mutant phenotype, suggesting the loss of a repressing complex. We believe that Hr78 is acting as an anchor for repressing and activating complexes and the NuA4/TIP60 complex helps repress genes that can negatively impact eye formation in the context of Lobe 2.